Enhanced NH3 and NO sensing performance of Ti3C2O2 MXene by biaxial strain: insights from first-principles calculations - Satchakorn Khammuang; Kantaphong Wongphen; Tanveer Hussain; Komsilp Kotmool (Physical Chemistry Chemical Physics, 2025)
and NO at low to room temperatures.
Keywords: MXene and MAX Phase Materials; 2D Materials and Applications; Boron and Carbon Nanomaterials Research